2015
DOI: 10.4103/0976-5042.159238
|View full text |Cite
|
Sign up to set email alerts
|

Role of endoscopy in evaluating upper gastrointestinal tract lesions in rural population

Abstract: Background and Objectives: Before the advent of endoscopy direct access to the lesion for the confirmation of the diagnosis was difficult, this posed difficulty in contemplating adequate and appropriate surgery. Endoscopy as a diagnostic and therapeutic tool has grown in recent years. Upper gastrointestinal (GI) endoscopy is one of the most fascinating branch which serves not only as a means of resolving or amplifying the diagnosis made clinically or by X-ray, but also a primary diagnostic procedure for condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
4
7
0
Order By: Relevance
“…However, Increased incidence of 4.6% was reported by Javali et al and Khan Y et al in other regions. 4,14 The incidence of oesophageo gastric junction carcinoma in the present study was 0.3%, consistent with the study of Antony B et al was 0.5% and by Khaliq M et al was 0.2%. 3,7 The miscellaneous pathologies as in Table 1 was 5.9% which was slightly greater than the study done by Khan Y et al at 3.5% and lower than 7% reported by Khaliq M et al 7,14 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, Increased incidence of 4.6% was reported by Javali et al and Khan Y et al in other regions. 4,14 The incidence of oesophageo gastric junction carcinoma in the present study was 0.3%, consistent with the study of Antony B et al was 0.5% and by Khaliq M et al was 0.2%. 3,7 The miscellaneous pathologies as in Table 1 was 5.9% which was slightly greater than the study done by Khan Y et al at 3.5% and lower than 7% reported by Khaliq M et al 7,14 …”
Section: Discussionsupporting
confidence: 92%
“…The proportion of normal study in the Institution was 6% which is less compared with other studies (Table 4). 4.45% -2.89 -Shresta R et al reported the incidence of gastritis at 41.6% which was almost to equivalent to the present study of 44.1%. 9 On comparing the data with other rural population, the incidence of gastritis was found to be high in all the studies compared to other diseases irrespective of rural or urban study (Table 4).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In study done by Javali et al the incidence of gastritis was 26.13%. 2 Similar study done by Chandial et al, the incidence of gastritis was 21.7%. 4 In a similar study done by Kunar et al the incidence of gastritis was 30%.…”
Section: Gastritissupporting
confidence: 75%
“…A similar study conducted by Javali et al role of endoscopy in evaluating upper gastrointestinal tract lesions in rural population. 2 Male predominance was seen 61.6%. Majority of cases were in 61 and above.…”
Section: Resultsmentioning
confidence: 94%